Cardiovascular risk factors and outcomes in early rheumatoid arthritis: a population-based study. Issue 20 (24th March 2020) - Nikiphorou, Elena; de Lusignan, Simon; Mallen, Christian D; Khavandi, Kaivan; Bedarida, Gabriella; Buckley, Christopher D; Galloway, James; Raza, Karim
Abstract : Objective: To assess the burden of cardiovascular disease (CVD) at and prior to diagnosis in people with early rheumatoid arthritis (RA) and subsequent CVD in these patients. Methods: A retrospective case–control study using a large English primary care database. People with RA (n=6591) diagnosed between 2004 and 2016 (inclusive) were identified using a validated algorithm, matched 1:1 by age and gender to those without RA (n=6591) and followed for a median of 5.4 years. We assessed differences in CVD at, before and after diagnosis, and the impact of traditional and RA-related risk factors (C reactive protein, RA-related autoantibodies and medication use) on incident CVD (a composite of myocardial infarction (MI), stroke or heart failure). Results: RA cases and their matched controls were both of mean age 58.7 (SD 15.5) at cohort entry, and 67.5% were female. Some CVD risk factors were more common at RA diagnosis including smoking and diabetes; however, total and low-density lipoprotein cholesterol were lower in patients with RA. CVD was more common in RA at cohort entry; stroke (3.9% vs 2.7%, p<0.001), heart failure (1.6% vs 1.0%, p=0.001), and non-significantly MI (3.1% vs 2.8%, p=0.092). Excess CVD developed in the 5 years preceding diagnosis. After adjustment for traditional and RA-related risk factors, RA was associated with greater risk of post-diagnosis CVD (HR 1.33, 95% CI 1.07 to 1.65, p=0.010). Conclusions: An excess of stroke and heart failure occurs before diagnosis of RA. There is excess risk for further cardiovascular events after diagnosis, which is not explained by differences in traditional CVD or RA-related risk factors at diagnosis.